2020
DOI: 10.1186/s40580-020-00223-w
|View full text |Cite
|
Sign up to set email alerts
|

Simple, rapid, and accurate malaria diagnostic platform using microfluidic-based immunoassay of Plasmodium falciparum lactate dehydrogenase

Abstract: This work reports on a rapid diagnostic platform for the detection of Plasmodium falciparum lactate dehydrogenase (PfLDH), a representative malaria biomarker, using a microfluidic microplate-based immunoassay. In this study, the microfluidic microplate made it possible to diagnose PfLDH with a small volume of sample (only 5 μL) and short time (< 90 min) compared to conventional immunoassays such as enzyme-linked immunosorbent assay (ELISA). Moreover, the diagnostic performance of PfLDH showed high sensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Furthermore, the functionalization procedure of PIT can be carried out by a simple UV lamp in a few minutes, thus we anticipate that such an approach can be carried out in low resource settings which would be critical for many malaria diagnostic applications. Therefore, we foresee that our approach may provide a solution to the cold transport challenges common to the presently used immunochromatographic lateral flow assays 45 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the functionalization procedure of PIT can be carried out by a simple UV lamp in a few minutes, thus we anticipate that such an approach can be carried out in low resource settings which would be critical for many malaria diagnostic applications. Therefore, we foresee that our approach may provide a solution to the cold transport challenges common to the presently used immunochromatographic lateral flow assays 45 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The conventional serologic antibody-based rapid diagnostic tests rely upon the Pf LDH detection in pretreated blood and offer rapid and cost-effective malaria diagnosis. However, the poor LOD as well as the transportation and storage difficulties of pre-functionalized devices in tropical environment make such tests unfit for early diagnosis and screening 45 47 . The ultrasensitive PEF-based device in combination with a unique functionalization procedure (PIT), which can be accomplished in a few minutes, results in an immunosensor suitable for detecting Pf LDH at femtomolar level in the whole blood without any pretreatment and preconcentration steps.…”
Section: Introductionmentioning
confidence: 99%
“…The microfluidic microplate is a spiral microfluidic channel with 1.5 times larger surface area and 50 times larger surface area-to-volume ratio compared to conventional ELISA plates. The detection limit is as low as 6.25 × 10 −3 U/L [ 43 ]. However, the UV spectrum also will be easily affected by the external environment, such as the color of the sample [ 70 ].…”
Section: Ldh Detection Methodsmentioning
confidence: 99%
“…For instance, numerous studies have reported LDH as a prognostic biomarker for colorectal cancer [ 32 , 33 ], lung cancer [ 34 , 35 ], melanoma [ 36 , 37 ], renal cell cancer [ 38 , 39 ] and hepatocellular carcinoma [ 40 , 41 ]. Many studies have also shown that LDH is also a biomarker for malaria [ 42 , 43 , 44 ]. Moreover, LDH activity is an important clinical guide to the choice of chemotherapy and helps to identify whether a pleural effusion is benign or malignant [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cefadroxil and amoxicillin, which have very similar structures, remarkably showed adequate separation. This sensor has also been used to diagnose diseases [95][96][97][98][99].…”
Section: Genetic Engineering For Functional Peptide Generation On M13...mentioning
confidence: 99%